The 22q11.2 deletion syndrome as a model for idiopathic scoliosis – A hypothesis. (June 2019) - Homans, Jelle F.; de Reuver, Steven; Breetvelt, Elemi J.; Vorstman, Jacob A.S.; Deeney, Vincent F.X.; Flynn, John M.; McDonald-McGinn, Donna M.; Kruyt, Moyo C.; Castelein, René M.
Abstract: Adolescent idiopathic scoliosis (AIS), defined as a lateral deviation of the spine of at least ten degrees, is a classic enigma in orthopaedics and affects 1–4% of the general population. Despite (over) a century of intensive research, the etiology is still largely unknown. One of the major problems in all existing AIS research is the fact that most patients come to medical attention after onset of the curve. Therefore, it is impossible to know whether current investigated parameters are causative, or an effect of the scoliosis. Moreover, up until now there is no known animal model that captures the core features of AIS. In order to identify causal pathways leading to AIS we propose another approach, which has been of great value in other medical disciplines: To use a subset of the population, with a higher risk for a certain disease as a "model" for the general population. Such a "model" may allow the identification of causative mechanisms that might be applicable to the general population. The 22q11.2 deletion syndrome (22q11.2DS) is the most common microdeletion syndrome and occurs in ∼1:3000–6000 children and 1:1000 pregnancies. Nearly half of the population of patients with 22q11.2DS develop a scoliosis that in most cases resembles AIS as far as age at onset and curve pattern. We postulate that within 22q11.2DS certain causal pathways leading to scoliosis can be identified and that these are applicable to the general population.